2011
DOI: 10.1007/s00256-011-1119-1
|View full text |Cite
|
Sign up to set email alerts
|

CT-guided percutaneous cryoablation of osteoid osteoma in children: an initial study

Abstract: Percutaneous cryoablation is safe and effective for the treatment of osteoid osteomas in children. Notably, this procedure can be accomplished without general anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 24 publications
1
20
0
Order By: Relevance
“…To the best our knowledge, there are yet to be any studies on the use of cryoablation in establishing an ONFH animal model. The present study used an argon-based system, as discussed in a number of previous studies (1215), to establish an ONFH animal model. Under the guidance of MRI, the probes can be maintained in the correct position in every femoral head.…”
Section: Discussionmentioning
confidence: 99%
“…To the best our knowledge, there are yet to be any studies on the use of cryoablation in establishing an ONFH animal model. The present study used an argon-based system, as discussed in a number of previous studies (1215), to establish an ONFH animal model. Under the guidance of MRI, the probes can be maintained in the correct position in every femoral head.…”
Section: Discussionmentioning
confidence: 99%
“…Cryoablation involving rapidly freezing temperatures within the target tissues, followed by rapid active thawing leading to cellular death through immediate and delayed mechanisms, has also been described. [23][24][25] Arthroscopic excision has also been found to have excellent functional results when used for intraarticular hip lesions.…”
Section: Osteoid Osteomamentioning
confidence: 99%
“…12 Cryoablation is growing momentum as a method to treat benign and malignant musculoskeletal neoplasms. Currently only used in selective cases, several trials demonstrated safety and efficacy in the treatment of OO, [14][15][16] an entity usually treated with RFA. The most common complications described with cryoablation are damage to skin, neural injury, muscle injury, pathologic fracture, and tumor lysis.…”
Section: Cryoablationmentioning
confidence: 99%